2017
DOI: 10.1063/1.4977735
|View full text |Cite
|
Sign up to set email alerts
|

Distortion dependent intersystem crossing: A femtosecond time-resolved photoelectron spectroscopy study of benzene, toluene, and p-xylene

Abstract: The competition between ultrafast intersystem crossing and internal conversion in benzene, toluene, and p-xylene is investigated with time-resolved photoelectron spectroscopy and quantum chemical calculations. By exciting to S2 out-of-plane symmetry breaking, distortions are activated at early times whereupon spin-forbidden intersystem crossing becomes (partly) allowed. Natural bond orbital analysis suggests that the pinnacle carbon atoms distorting from the aromatic plane change hybridization between the plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 80 publications
2
15
0
Order By: Relevance
“…Besides an overall similar spectral pattern, an interesting difference lies in that blue ESA intensity is ∼30% smaller than red ESA upon 560 nm excitation (Figure S4a), whereas both features have a largely equal intensity upon 400 nm excitation (Figure c). This unexpected result supports the importance of performing the excitation-dependent TA measurements and comparing the retrieved electronic dynamics that report on photophysics and/or photochemistry pathways, which suggests that ultrafast ISC occurs more for dimethylxylindein in DCM with a bluer excitation, consistent with some literature that excitations to higher-lying electronic states could lead to higher triplet yields. , The reduction of the long-time components of blue, red ESA bands (25, 2.5 ns in Figure S4a) versus those of 400 nm excitation (40, 8.0 ns in Figure c) provides further evidence for the diminishment of T x formation after 560 nm excitation, although with a limited time window (see SI methods) this component likely represents an average S 1 /T 1 lifetime with some uncertainty.…”
Section: Results and Discussionsupporting
confidence: 88%
“…Besides an overall similar spectral pattern, an interesting difference lies in that blue ESA intensity is ∼30% smaller than red ESA upon 560 nm excitation (Figure S4a), whereas both features have a largely equal intensity upon 400 nm excitation (Figure c). This unexpected result supports the importance of performing the excitation-dependent TA measurements and comparing the retrieved electronic dynamics that report on photophysics and/or photochemistry pathways, which suggests that ultrafast ISC occurs more for dimethylxylindein in DCM with a bluer excitation, consistent with some literature that excitations to higher-lying electronic states could lead to higher triplet yields. , The reduction of the long-time components of blue, red ESA bands (25, 2.5 ns in Figure S4a) versus those of 400 nm excitation (40, 8.0 ns in Figure c) provides further evidence for the diminishment of T x formation after 560 nm excitation, although with a limited time window (see SI methods) this component likely represents an average S 1 /T 1 lifetime with some uncertainty.…”
Section: Results and Discussionsupporting
confidence: 88%
“…However, the key issue of the purely organic RTP emitters having an afterglow emission feature in the amorphous powder at ambient conditions is ill understood. Ideally, molecular rigidity as well as energetic close proximity (Δ E S1–T1 ) of the singlet (S 1 ) state and triplet manifolds (T n ) are required to observe the RTP feature. ,, Because Δ E S1–T1 is inversely proportional to the perturbation factor (δ) that describes SOC, it turns out that the δ increases with a greater value of the spin–orbit matrix element induced by heavy atoms , and molecular distortion , and lowering of Δ E S1–T1 . The Δ E S1–T1 , on the other hand, can be controlled by aggregation as well as angular orientation of the donor and acceptor. , In recent studies, afterglow emission has been realized mainly through ordered packing in the crystals that favor exciton migration. Moreover, recently rigid-host matrixes , that reduce nonradiative pathways due to oxygen diffusion and molecular vibrations have also been employed to observe persistent RTP (pRTP).…”
mentioning
confidence: 99%
“…Ideally, molecular rigidity as well as energetic close proximity (ΔE S1−T1 ) of the singlet (S 1 ) state and triplet manifolds (T n ) are required to observe the RTP feature. 4,16,17 Because ΔE S1−T1 is inversely proportional to the perturbation factor (δ) that describes SOC, 21 it turns out that the δ increases with a greater value of the spin−orbit matrix element induced by heavy atoms 5,14 and molecular distortion 22,23 and lowering of ΔE S1−T1 . The ΔE S1−T1 , on the other hand, can be controlled by aggregation 24 as well as angular orientation of the donor and acceptor.…”
mentioning
confidence: 99%
“…ISCs are forbidden in spin-free quantum mechanics but can be mediated by spin-orbit coupling (SOC). SOC tends to be small for systems without heavy metals, which historically led many to believe that ISC would be slow compared with IC rates, but recent work has shown that ISC can occur at short times, even in small molecules, 1 and may compete with IC in some systems. 2 Moreover, even though most photoexcited systems start in a singlet state, excited state triplets are usually lower in energy than excited state singlets due to antisymmetry and exchange; thus, ISC is usually possible thermodynamically.…”
Section: Introductionmentioning
confidence: 99%